2017
DOI: 10.5507/fot.2017.012
|View full text |Cite
|
Sign up to set email alerts
|

Tritium influence on morphology, reactive oxygen species production and catalase gene expression in Pseudendoclonium basilense and Stigeoclonium nanum (Chlorophyta)

Abstract: Abstract:The response of two strains of Pseudendoclonium basilense viscHer and Stigeoclonium nanum (dillwyn) kützing to ionizing radiation was studied under laboratory conditions. Both strains were isolated as epiphytic from stagnant water bodies under ambient levels of ionizing radiation and cultivated under laboratory conditions on a gradient of tritiated water diluted in liquid Bold´s basal medium. Exposure to low doses of ionizing radiation stimulated changes in cell dimensions and morphology of in both st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The luminescent marine bacteria naturally increased the ROS content in aqueous media, and additionally increased the ROS production up to 300% in the presence of tritium [79]. Hašler et al [129] confirmed that tritiated water can stimulate the ROS production in another type of bacteria, Pseudendoclonium basilense, a bacterial strain from standing water. The 300% activation of luminescence of marine bacteria by tritiated water was attributed to the 'bystander effect' [79].…”
Section: Active Role Of Reactive Oxygen Speciesmentioning
confidence: 98%
“…The luminescent marine bacteria naturally increased the ROS content in aqueous media, and additionally increased the ROS production up to 300% in the presence of tritium [79]. Hašler et al [129] confirmed that tritiated water can stimulate the ROS production in another type of bacteria, Pseudendoclonium basilense, a bacterial strain from standing water. The 300% activation of luminescence of marine bacteria by tritiated water was attributed to the 'bystander effect' [79].…”
Section: Active Role Of Reactive Oxygen Speciesmentioning
confidence: 98%